Diritto alla salute mentale e sistema penitenziario - Angeli, Valentina; Renzaglia, Beatrice (Il sogno della farfalla, 2022)
The aim of this article is to briefly describe the Italian normative framework in act for the protection of the right to mental health, with a particular reference to the penitentiary context. The authors, starting from some general consideration about the right to health, move into an analysis of the effectiveness of the current normative system, with a specific focus on its legislative and jurisprudential evolution over the last years.